Remarkable Natural Material Surfaces and Their Engineering Potential - Lee, Michelle.; Lee, Michelle. (Springer International Publishing : Imprint: Springer, 2014)
This book explores a collection of natural surfaces, their scientific characteristics, and their unique engineering potential – demonstrating that engineering applications can be found in unexpected places. The surfaces covered range from botanical ones, like rice and lotus leaves, to insect surfaces, like butterfly and dragonfly wings. The variety of surfaces and numerous engineering potentials described show how biomimicry can be utilized to solve countless real-world problems.